Unhealthy alcohol use and intimate partner violence among men and women living with HIV in Uganda. - Miller, Amanda P.; Fatch, Robin; Lodi, Sara; Marson, Kara; Emenyonu, Nneka; Kekibiina, Allen; Beesiga, Brian; Chamie, Gabriel; Muyindike, Winnie R.; Hahn, Judith A. (BMC public health, 2022)
Background: Intimate partner violence (IPV) and alcohol use are interrelated public health issues. Heavy and frequent alcohol use increase the risk of IPV, but the relationship between alcohol use and IPV (including recent and lifetime IPV victimization and perpetration) has not been well described among persons living with HIV (PWH) in sub-Saharan Africa. Methods: We used baseline data from the Drinker’s Intervention to Prevent Tuberculosis study. All participants were PWH co-infected with tuberculosis and had an Alcohol Use Disorders Identification Test – Consumption (AUDIT-C) positive score (hazardous drinking) and positive urine ethyl glucuronide test, indicating recent drinking. High-risk drinking was defined as AUDIT-C > 6 and/or alcohol biomarker phosphatidylethanol (PEth) ≥ 200 ng/mL. We measured IPV using the Conflict Tactics Scale. We estimated the association between alcohol use level and recent (prior six months) IPV victimization (recent perpetration was too low to study) using multivariable logistic regression models adjusted for gender, age, assets, education, spouse HIV status, religiosity, depressive symptoms, and social desirability. We additionally estimated the interaction of alcohol use and gender on IPV victimization and the association between alcohol use and lifetime victimization and perpetration. Results: One-third of the 408 participants were women. Recent IPV victimization was reported by 18.9% of women and 9.4% of men; perpetration was reported by 3.1% and 3.6% of women and men. One-fifth (21.6%) of those reporting recent IPV victimization also reported perpetration. In multivariable models, alcohol use level was not significantly associated with recent IPV victimization (p = 0.115), nor was the interaction between alcohol use and gender (p = 0.696). Women had 2.34 times greater odds of recent IPV victimization than men (p = 0.016). Increasing age was significantly associated with decreased odds of recent IPV victimization (p = 0.004). Conclusion: Prevalence of IPV victimization was comparable to estimates from a recent national survey, while perpetration among men was lower than expected. Alcohol use level was not associated with IPV victimization. It is possible that alcohol use in this sample was too high to detect differences in IPV. Our results suggest that women and younger PWH are priority populations for IPV prevention.
Keywords: Intimate partner violence; Alcohol use; HIV; Uganda